If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-8)*2=(3-x)*2
We simplify the equation to the form, which is simple to understand
(x-8)*2=(3-x)*2
Reorder the terms in parentheses
(+2x-16)=(3-x)*2
Remove unnecessary parentheses
+2x-16=(3-x)*2
Reorder the terms in parentheses
+2x-16=(+6-2x)
Remove unnecessary parentheses
+2x-16=+6-2x
We move all terms containing x to the left and all other terms to the right.
+2x+2x=+6+16
We simplify left and right side of the equation.
+4x=+22
We divide both sides of the equation by 4 to get x.
x=5.5
| 0.3(x-2)=6 | | 3v^7-12v^5= | | -6*y-(-6)*1=6y | | k^4-5k^2+4= | | 9-3y-17=-11-5y+15 | | 10+15-10=15+10-5+5 | | 7x+3=4x+36 | | 10+15-10=15+10-10 | | 16-9+10=18+177-100 | | -1=2x | | 16-9+10=18+177-100+273 | | .5x^2+x=264 | | 0.6x^2=1.23+0.6 | | x^2-3=18-9x^2 | | -5t^8-20t^7-15t^6= | | x^2+27x+182=462 | | 5(3+3x)-4=26 | | (x-9)(x+7)=(x+4)*2 | | 1x+3=3x+4 | | 9-b^2= | | (x-9)(x+7)=(x+4)2 | | x=-2x^2-2x-1 | | 32=.5[(x+6)+(x+2)]x | | -(4x-7)=-(2x-1) | | a+5=-5a-5 | | 4x-3=x+14 | | x^2+1x-306=0 | | x^2+1x-3-6=0 | | 84=16x^2+10x | | x^2+2x-728=0 | | x^2+2-728=0 | | -2(8+4d)=-4(-3d-6) |